A two-level staging system for the embryonic morphogenesis of the Mediterranean fruit fly (medfly) Ceratitis capitata. - Frederic Strobl; Alexander Schmitz; Marc F Schetelig; Ernst H K Stelzer (PLoS ONE)
Comparative studies across multiple species provide valuable insights into the evolutionary diversification of developmental strategies. While the fruit fly Drosophila melanogaster has long been the primary insect model organism for understanding molecular genetics and embryonic development, the Mediterranean fruit fly Ceratitis capitata, also known as medfly, presents a promising complementary model for studying developmental biology. With its sequenced genome and a diverse array of molecular techniques, the medfly is well-equipped for study. However, an integrative framework for studying its embryogenesis is currently lacking. In this study, we present a two-level staging system for the medfly based on nine datasets recorded using light sheet fluorescence microscopy. The upper level features of six consecutive embryogenetic events, facilitating comparisons between insect orders, while the lower level consists of seventeen stages, adapted from the fruit fly, allowing for comparisons within the Diptera. We provide detailed descriptions of all identifiable characteristics in multiple formats, including a detailed timetable, comprehensively illustrated figures for all embryogenetic events, glossary-like tables for selected structures and processes, as well as a stage-based quick lookup chart. One remarkable difference between the fruit fly and the medfly is that in the latter, the amnioserosa differentiates and unfolds already during gastrulation. Our staging system, which is based on systematically acquired fluorescence live imaging data, provides standard deviations for each developmental time point and serves as a template for future studies seeking to establish an integrative morphogenic framework for other emerging model insect species.